ANALISIS PENGARUH INFORMASI LABA AKUNTANSI, NILAI BUKU EKUITAS DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM - Rio Iustian; Dista Amalia Arifah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
This study aims to analyze the influence of Earnings, Book Value of Equity and Operational Cah Flow on Stock Price. Sample of this research consist 64 of manufacturing firms which is listed in Indonesian Stock Exchange from 2008 until 2010. Data used in this research are financial statement and closing stock price publication of financial statement date which is obtain from PRPM in Indonesian Stock Exchange, Capital Market Directory (CMDI) andIndonesian Stock Exchange website (www.co.idx.id). The statistic method used to test on the research hypothesis ismultiple regression. To analyzed the data using software SPSS ver. 15.0. The result of these study show that: (1) variable earnings had an influence and positive value relevance to stock price in partial; (2) variable book value of equity had an influence and positive value relevance to stock price in partial; (3) in partial operation cash flows had no significant influence but had a positive relevance value to stock price.